Is it (cyber)bullying?: Assessing adult perceptions of bullying and cyberbullying using a mixed-methods approach - Bryson, Sara (Deviant behavior, 2024)
Despite decades of research on bullying and the influx of studies examining cyberbullying, there is no universal definition for either term. The lack of clarity in defining these terms may impact individuals’ ability to identify (cyber)bullying. Most prior research on bullying and cyberbullying has surveyed school children, their peers, and teachers about their experiences. However, much less research has examined if members of the general public can identify bullying and cyberbullying outside of the school setting. Therefore, the overall objective of the current study is to investigate adults’ ability to identify bullying and cyberbullying and examine the rationale for why respondents identified - or not - instances of verbal, physical, and cyberbullying. Data were collected from 652 adults aged 18 to 50 years old who were residing in the United States. Results suggest that most respondents identified each scenario as (cyber)bullying, however, the rationale behind their decisions varied. Seven themes were identified (e.g. repetition, power imbalance) as both reasons participants identified a situation as a form of bullying, along with reasons why they did not believe a situation was a form of bullying. Implications for policy, practice, and research are provided.